Kajian Sosiologi Kesehatan Pada Keluarga Pasien Kanker di Yayasan Peduli Kanker Anak Bali (JURNAL ILMIAH SOSIOLOGI: SOROT, 2023)
This research focuses on the study of Sociology of Health in families with children as cancer patients at the Yayasan Peduli Kanker Anak Bali. The purpose of this study is to describe and analyze interventions and challenges faced by families in assisting children as cancer patients, including the role of foundations for families and children with cancer at the Yayasan Peduli Kanker Anak Bali. The method used in this paper is qualitative with a descriptive-explanative type. The theory used to analyze this research is the behavior change model from Lawrence Green (1980). The results of the study show that in accompanying children as cancer patients, families, especially parents, must face various challenges and obstacles such as lack of knowledge, lack of dissemination of information related to cancer and completeness of health administration which then has an impact on other aspects. Once the challenges that must be faced are complex, it puts parents in a position to be able to intervene with children in treatment, care, or in daily activities. Children as cancer patients cannot face challenges alone and make decisions for themselves. Children depend on their parents as the closest people for their lives. The presence of the Yayasan Peduli Kanker Anak Bali in helping families accompany children as cancer patients is shown through various roles and efforts in providing comfort, easy access to health facilities, and protection for parents and child cancer patients during underwent period of treatment and care at Rumah Sakit Umum Pusat Prof. Dr. I.G.N.G Ngoerah Denpasar. The role of mentoring shown by the foundation is also able to bring changes to the health behavior of families of child cancer patients. Keywords: child, intervention, cancer, family, health